Explanatory Models of Illness and Psychiatric Rehabilitation: A Clinical Sociology Approach - Sévigny, Robert; Chen, Sheying; Chen, Elaina Y. (Qualitative Sociology Review, 2010)
The notion of explanatory models of illness (EMI) epitomizes the theme of social representation in social psychiatry. This article illustrates a clinical sociology approach to the subject by revisiting the seminal work of Kleinman and reflecting on the use of EMI in studying severe mental illnesses, particularly in China. A general literature review is provided to show the complexity of the subject, and the work of clinical sociologist Sévigny over the past two decades is summarized. A case analysis is conducted to illuminate the many social factors that came to play in affecting the experiences and perceptions of schizophrenic patients and their significant others in the nation’s capital Beijing in the 1990s. Diverse “explanations” in the experience of schizophrenia are explored, including the medical, the psychogenic, and the psychosocial models, among such others as inheritance and religious beliefs. Implications for research and clinical practice are discussed, including extending EMI study beyond illness interpretation to emphasize social rehabilitation.